论王昭君形象在古代戏曲与现代戏剧文本中的不同呈现方式 = An Investigation on the representations of Wang Zhaojun in traditional opera and modern drama - 徐晓慧 Swee, Siow Hui (2011)
综观许多有关王昭君形象的研究，发现许多学者对王昭君这个人物进行了研究。众多学者从各方面对昭君形象进行了分析，但尚未发现有对古今戏中王昭君形象的呈现方式做出分类与分析的研究。本文在第二章做了简单的文本介绍，在细读四个文本的故事内容及梳理之后，发现不同时代的文本所塑造的人物、故事情节等等都有所不同。不同之中又有所相同之处，是笔者观察到的一个特征。在第三章中，对于古今文本不同的呈现方式做了仔细的分析，并将其不同的呈现方式归纳为四种，即王昭君的形象与性格、王昭君与汉元帝、王昭君出塞的故事和塑造人物的表现手法。最后，在第四章中为影响呈现方式不同的因素做出了分析，其中包括了时代因素、作者创作因素及传播因素。本文将以四个古今文本为例，即元代《汉宫秋》、明代《昭君出塞》、及现代的郭沫若剧作《王昭君》和曹禺的《王昭君》，探讨这四个文本中王昭君形象呈现方式的不同，并将各文本中的呈现方式进行比较，然后总结这些影响古代戏曲文本和现代戏剧文本中昭君形象不同的因素。The story of Wang Zhaojun has been an interesting research topic in Chinese popular literature. Many scholars have explored the development and evolvement of the image of Wang Zhaojun appeared in different dramatic texts, but I have not seen any work done specifically in comparative study of the representation of Wang Zhaojun in traditional opera and modern drama. I will be using two texts from the classical drama and two texts written for the contemporary dramatic stage for my study. These texts are: the Yuan drama Han Gong Qiu (“Autumn in the Han Palace”) and Ming drama Zhaojun Chusai (“Zhaojun Leaving for the Frontier”); and two modern dramas both bearing the same title Wang Zhaojun, written by Cao Yu and Guo Moruo.